Sex Disparity in How Pain Sensitivity Influences Dry Eye Symptoms. Issue 10 (October 2019) - Li, Wing; Lin, Meng C.
Abstract : Purpose: Women have a higher dry eye disease prevalence compared with men, although only relatively minor differences in the ocular surface have been observed. Interestingly, a sex difference in pain sensitivity is known, and recent research suggests that pain sensitivity is associated with dry eye symptoms. This study attempts to discern whether the association between pain sensitivity and dry eye symptoms varies between women and men. Methods: In this prospective cross-sectional study, subjects were seen for one visit where they were asked to fill out a set of questionnaires consisting of the Pain Sensitivity Questionnaire, Ocular Surface Disease Index (OSDI), and other dry eye questionnaires. This was followed by an ocular surface assessment on both eyes. Results: Two hundred eighty-seven subjects (194 women, 93 men) completed the study. Intersex differences in the ocular surface were noted. Even after accounting for these differences, an interaction effect between sex and Pain Sensitivity Questionnaire-minor score on dry eye symptoms was observed, with only women noting increased symptoms on the OSDI ( P < 0.005) and other dry eye questionnaires ( P values ranging from 0.01 to <0.005) with greater pain sensitivity. After controlling for other variables, women with the highest pain sensitivity had a 17-point higher OSDI score and greater symptoms, as reported by all the other dry questionnaires compared with their male counterparts. Conclusions: The role of pain sensitivity on dry eye symptoms appears to vary between women and men. This difference provides insight into why women have a significantly higher dry eye disease prevalence than men.